Adolescents' Perspectives on Personal and Societal Responsibility for Childhood Obesity — The Study of Beliefs through 'Serious' Game (PlayDecide). (25th February 2018) - Timotijevic, Lada; Acuna‐Rivera, Marcela; Gemen, Raymond; Kugelberg, Susanna; McBarron, Kate; Raats, Monique M.; Zolotonosa, Maria
Abstract : The dominant approaches to public health policy on childhood obesity are based on the neoliberal emphasis of personal choice and individual responsibility. We study adolescents' ( N = 81) beliefs about responsibility for childhood obesity as a public health issue, through an innovative participatory method, PlayDecide, organised in two countries: the UK and Spain. There is no evidence of a blanket rejection of individual responsibility, rather, a call for renegotiation of the values that inform adolescents' food choices. The findings suggest the need to broaden the framing of obesity‐related policy to go beyond the nutritional paradigm and include other values that signal health.